Interculturality in urban schools - Valqui, Jairo (2012)
This paper investigates the inclusion of the intercultural education in the urban school. To achieve this goal, we analyze the school’s official documents, the conception about interculturality from the teachers and parents, and the school practice. The observation reports that intercultural education has not been included into the urban school, because there is not any consistent relationship among the elements of this educational proposal.